Comparison of Serological Biomarkers in Rheumatoid Arthritis and Their Combination to Improve Diagnostic Performance - Martinez-Prat, Laura; Nissen, Michael J.; Lamacchia, Céline; Bentow, Chelsea; Cesana, Laura; Roux-Lombard, Pascale; Gabay, Cem; Mahler, Michael (Frontiers in Immunology, 2018)
Introduction The diagnosis of Rheumatoid Arthritis (RA) is based on a combined approach that includes serological markers such as Rheumatoid Factor (RF) and Anti-Citrullinated Peptide/Protein Antibodies (ACPA). The goal of this study was to evaluate the clinical performance of several RF and ACPA immunoassays for the diagnosis of RA, as well as the diagnostic value of a combinatory approach with these markers. Methods The study cohort included 1655 patients from the Swiss Clinical Quality Management (SCQM) registry with sera from 968 patients with RA and 687 disease controls, including patients with Axial Spondyloarthritis (axSpA) (n=450) and Psoriatic Arthritis (PsA) (n=237). ACPA were determined by anti-CCP2 IgG ELISA, QUANTA Flash® CCP3 IgG (CIA) and QUANTA Lite® CCP3 IgG ELISA. RF was determined by ELISA (QUANTA Lite® RF IgM, RF IgA and RF IgG) and with two research use only CIAs (QUANTA Flash® RF IgM and RF IgA). Results All three ACPA assays showed good discrimination between RA patients and controls and good clinical performance. Overall, CCP3 performed better than CCP2. More pronounced differences were observed between the RF assays. We observed that CIA platforms for both RF IgM and RF IgA showed better performance than the ELISA platforms. Excellent and good total agreements were found between ELISA and CIA for CCP3 (total agreement 95.3%, Kappa = 0.90), and between CCP2 and CCP3 ELISA (total agreement 86.6%, kappa = 0.73), respectively. RF IgM CIA and ELISA had a good qualitative agreement (86.5%, kappa = 0.73); RF IgA CIA and ELISA showed a moderate total agreement (78.5%, kappa =0.53). When combinatory analyses were performed, the likelihood of RA increased with dual positivity and triple positivity and combining different markers resulted in higher odds ratio than the individual markers in all cases. Conclusion ACPA and RF showed good clinical performance in this large Swiss cohort of RA patients and controls. Overall, the performance of CCP3 was superior to CCP2. The combination of these biomarkers in an interval model represents a potential tool for the diagnosis of RA patients.